2017
DOI: 10.1186/s12882-017-0460-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluid overload is an independent risk factor for acute kidney injury in critically Ill patients: results of a cohort study

Abstract: BackgroundAcute Kidney injury (AKI) is common and increases mortality in the intensive care unit (ICU). We carried out this study to explore whether fluid overload is an independent risk factor for AKI.MethodsSingle-center prospective, observational study. Consecutively admitted, ICU patients were followed for development of AKI. Intravenous fluid volumes, daily fluid balances were measured, hourly urine volumes, daily creatinine levels were recorded.ResultsThree hundred thirty nine patients were included; AKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 31 publications
(35 reference statements)
3
49
1
5
Order By: Relevance
“…In adult patients admitted to the ICU with sepsis, Van Biesen et al showed that a positive fluid balance on day 1 was associated with an increased risk of AKI . This was confirmed in a single‐center prospective observational study which demonstrated that positive fluid balance in the first 24 hours of ICU admission was associated with a significant increase in AKI . In patients admitted to Guy's & St. Thomas Hospital with stage 1 AKI, positive fluid balance was also found to be an independent predictor of progression to stage 3 AKI …”
Section: Recognition and Treatment Of Volume Overloadmentioning
confidence: 61%
See 1 more Smart Citation
“…In adult patients admitted to the ICU with sepsis, Van Biesen et al showed that a positive fluid balance on day 1 was associated with an increased risk of AKI . This was confirmed in a single‐center prospective observational study which demonstrated that positive fluid balance in the first 24 hours of ICU admission was associated with a significant increase in AKI . In patients admitted to Guy's & St. Thomas Hospital with stage 1 AKI, positive fluid balance was also found to be an independent predictor of progression to stage 3 AKI …”
Section: Recognition and Treatment Of Volume Overloadmentioning
confidence: 61%
“…9 This was confirmed in a single-center prospective observational study which demonstrated that positive fluid balance in the first 24 hours of ICU admission was associated with a significant increase in AKI. 10 In patients admitted to Guy's & St. Thomas Hospital with stage 1 AKI, positive fluid balance was also found to be an independent predictor of progression to stage 3 AKI. 11 Even after adjusting for severity of illness, numerous studies in both children and adults have demonstrated an association between fluid overload and mortality in patients with AKI.…”
mentioning
confidence: 92%
“…Given the demonstrated morbidity associated with hypervolemia in critically ill patients, 27 , 43 45 the established benefits of “deresuscitation” in such patients, 43 , 46 and the absence of evidence of improved outcomes with volume administration to treat hypernatremia in resuscitated patients, we believe that a cautiously “salt-tolerant/fluid-restricted” therapeutic strategy is at least as well supported by existing research as is the dominant “salt-intolerant/fluid-liberal” paradigm.…”
Section: Discussionmentioning
confidence: 97%
“…In managing intra-abdominal hypertension and abdominal compartment syndrome, poorer outcomes have been attributed to fluid overload [89,90], a phenomenon linked to capillary leak and tissue edema. While fluid is often aggressively given to prevent AKI, the association between fluid overload and poorer renal outcomes has been evident [86,91,92], prompting questions on the cause-effect relationship between fluid overload and AKI [93].…”
Section: The Importance Of Fluid Balancementioning
confidence: 99%